2017
DOI: 10.3390/nu9010028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Vitamin D3 Hormone Administration on Anxiety-Like Behavior in Adult Female Rats after Long-Term Ovariectomy

Abstract: The present preclinical study was created to determine the therapeutic effects of vitamin D hormone treatment as an adjunctive therapy alone or in a combination with low dose of 17β-estradiol (17β-E2) on anxiety-like behavior in female rats with long-term absence of estrogen. Accordingly, the aim of the current study was to examine the effects of chronic cholecalciferol administration (1.0, 2.5 or 5.0 mg/kg subcutaneously, SC, once daily, for 14 days) on the anxiety-like state after long-term ovariectomy in fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 72 publications
2
29
1
Order By: Relevance
“…In this study, the ovariectomized group rats exhibited anxiety-like behavior as observed through OFT and EPM. This corroborated the findings of Fedotova et al that the anxiety-like state is enhanced in OVX rats compared with normal rats (Fedotova, Pivina, & Sushko, 2017). Meanwhile, OVX rats which were treated with EGCG showed a decreased anxiety-like state compared with untreated OVX rats.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the ovariectomized group rats exhibited anxiety-like behavior as observed through OFT and EPM. This corroborated the findings of Fedotova et al that the anxiety-like state is enhanced in OVX rats compared with normal rats (Fedotova, Pivina, & Sushko, 2017). Meanwhile, OVX rats which were treated with EGCG showed a decreased anxiety-like state compared with untreated OVX rats.…”
Section: Discussionsupporting
confidence: 90%
“…The aim of the present work was to clarify the anxiolyticlike effect of VD 3 at different doses and to further study the role of the BDNF signaling pathway, as well as the HPA axis, on a rat model of CUMS. As in prior research (Fedotova et al, 2017(Fedotova et al, , 2018Fedotova, 2019), we used long-term estrogen deficiency caused by a post-ovariectomy period of 3 months. This animal model is widely utilized in preclinical behavioral research producing a menopausal-like state in women (Bekku and Yoshimura, 2005).…”
Section: The Current Researchmentioning
confidence: 99%
“…For the sham operation, the same procedure was followed but without the amputation of the ovaries. This entire procedure was performed in line with previously published research (Fedotova et al, 2017).…”
Section: Ovariectomymentioning
confidence: 99%
See 2 more Smart Citations